PERAN BRAND AWARENESS MEMEDIASI PENGARUH DAYA TARIK IKLAN TERHADAP NIAT BELI MOBIL MEREK TOYOTA - Sari, Luh Gede Indah Permata; Suprapti, Ni Wayan Sri; Suparna, Gede (Buletin Studi Ekonomi, 2021)
The purpose of this study is to explain the role of brand awareness in mediating the effect of advertising attractiveness on purchase intentions of Toyota brand cars in Denpasar City. This research was conducted in Denpasar City by taking a purposive sample of 110 consumers, either those who do not own a car or those who already own a car but not the Toyota brand. Data was collected through an online survey using a questionnaire in the form of a google form in the period November 2020 and analyzed using calculated average statistics and path analysis. The results of the study show that all hypotheses are accepted. The advertising attractiveness has a positive and significant effect on brand awareness, Advertising attractiveness has a positive and significant effect on purchase intention, Brand awareness has a positive and significant effect on purchase intention, Brand awareness significantly mediates the effect of advertising attractiveness on purchase intention